Implementasi Model Pembelajaran Berdiferensiasi dalam Meningkatkan Kompetensi Bahasa Inggris Maritim Mahasiswa Perguruan Tinggi Pelayaran di Indonesia - Endah Fauziningrum; Encis Indah Suryani (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This study aims to examine the implementation of a differentiated learning model in improving maritime English language competency among maritime college students in Indonesia. The background of this study is based on the maritime world's need for graduates with good English language competency, especially in professional and technical contexts. The approach used was a mixed method, namely a combination of quantitative and qualitative methods within a classroom action research framework implemented over two learning cycles. Data were collected through English language competency tests, observations, and in-depth interviews. The results showed a significant increase in all aspects of maritime English competency. The highest increase occurred in speaking skills at 44.38%, while the lowest increase was in maritime vocabulary comprehension at 30.25%. After the implementation of the differentiated learning model, 78.33% of students were in the "Good" and "Very Good" competency categories. Although in the initial stages of implementation there were challenges in students' adaptation to learning methods that differ from conventional learning, these obstacles were successfully overcome through a project-based learning strategy. This strategy is considered the most effective because it is able to provide an authentic context and approximate the real conditions in the maritime workplace. Thus, it can be concluded that the differentiated learning model has proven effective in improving students' maritime English language competency. This study recommends the broader implementation of similar models in English language learning programs at maritime institutions.